Primary Epidermoid Tumors of the Cerebellopontine Angle: A Review of 47 Cases. Issue 7 (August 2016) - Yawn, Robert J.; Patel, Neil S.; Driscoll, Colin L.; Link, Michael J.; Haynes, David S.; Wanna, George B.; Thompson, Reid C.; Carlson, Matthew L.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To analyze disease presentation, treatment, and clinical course of a consecutive series of patients with primary cerebellopontine angle (CPA) epidermoids. Patients: Forty-seven consecutive patients with previously untreated CPA epidermoids. Intervention(s): Observation and microsurgery. Main Outcome Measures: Disease- and treatment-associated morbidity, recurrence. Results: Forty-seven patients (mean age 39 years; 53% women) were analyzed and the average duration of follow-up was 42 months. The most common presenting symptom was headache (27; 57%); 13 (28%) exhibited preoperative asymmetric sensorineural hearing loss, 3 (6%) facial nerve paresis, and 3 (6%) hemifacial spasm. Thirteen patients (28%) were initially observed over a mean interval of 56 months; however, five experienced disease progression requiring operation. Thirty-nine patients (83%) underwent surgical resection; 18 (46%) received gross total, 5 (13%) near total, and 16 (41%) aggressive subtotal resection. Three patients (8%) recurred at a median of 53 months; two after subtotal and one after gross total resection. Ninety-three percent of patients with useful hearing maintained serviceable hearing following treatment and one patient (3%) experienced mild long-term postoperative facial nerve paresis (HB II/VI). All patients with preoperative facial nerve paresis recovered normal function postoperatively. There were no episodes of stroke or death. Conclusions: Surgical intervention is effective in alleviating symptoms of cranial neuropathy and brainstem compression from CPA epidermoids. Gross total resection is preferred; however, aggressive subtotal removal should be considered with adherent or extensive disease as reoperation rates are low, even in the setting of aggressive subtotal resection. Conservative observation with serial imaging is a viable initial strategy in asymptomatic or minimally symptomatic patients.